2021
DOI: 10.3390/ijerph18105439
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multicomponent Group Psychological Intervention Program in Patients with Inflammatory Bowel Disease: A Randomized Trial

Abstract: (1) Background: Stress, anxiety, and depression have been identified as factors that influence the development of inflammatory bowel disease (IBD). The main aim of this study was to test the effectiveness of group multicomponent cognitive-behavioral therapy at reducing stress, anxiety, and depression, and improving quality of life and the clinical course of the disease. (2) Methods: A total of 120 patients were evaluated using the General Perceived Stress Scale, Scale of Stress Perceived by the Disease, the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“… Gracie et al (2018) demonstrated a bi-directional relationship between disease activity and psychological disorders in CD and UC, highlighting the potential impact of brain-gut axis activity on the natural history of IBD. Different studies have demonstrated the role of psychological therapies on quality of life in patients with IBD ( Knowles et al, 2013 ; Neilson et al, 2016 ; Gracie et al, 2017 , 2018 ; Bernabeu et al, 2021 ). These results reinforce the need for integration therapies that target inflammatory disease activity with novel interventions that aim to improve psychological well-being in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“… Gracie et al (2018) demonstrated a bi-directional relationship between disease activity and psychological disorders in CD and UC, highlighting the potential impact of brain-gut axis activity on the natural history of IBD. Different studies have demonstrated the role of psychological therapies on quality of life in patients with IBD ( Knowles et al, 2013 ; Neilson et al, 2016 ; Gracie et al, 2017 , 2018 ; Bernabeu et al, 2021 ). These results reinforce the need for integration therapies that target inflammatory disease activity with novel interventions that aim to improve psychological well-being in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies focused either on IBD in general (and not on CD specifically) or on single interventions rather than multimodal and comprehensive approaches. In particular, multicomponent psychological group interventions in IBD [26, 27] and a cognitive behavioral therapy in combination with mindfulness in CD [28] showed improvements in QoL. In addition, other research groups were able to show improvements also in stress levels as well as in anxiety and depression symptoms in patients with IBD through a combination of breathing exercises, meditation, and relaxation compared to the waiting list CG [29].…”
Section: Discussionmentioning
confidence: 99%
“…The trends we found were in line with the observations of other working groups. Single previous studies [26, 27, 35, 36] and a systematic review [33] on mindfulness-based or stress management-based interventions, as well as a program focusing on nutrition and exercise in patients with IBD [32], did not show significant impacts of such interventions on disease activity in IBD. However, stress management, relaxation, lifestyle modification, and yoga interventions resulted at least in improvement in clinical disease activity, primarily by reducing abdominal pain [31, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…CD and UC are considered psychosomatic diseases determined by biopsychosocial factors. Thus, IBDs require multidisciplinary care [50,51]. It appears that the prevalence of depressive and anxiety symptoms is similar between IBDs and other chronic somatic diseases [52].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the assessment of depressive symptoms should probably be considered as a standard element of disease activity evaluation, since the relationship appears to be bidirectional [5]. Taking into account the temperamental traits may help in providing patient-tailored therapeutic interventions and increase their effectiveness [50]. This appears important, since the history of patients' therapy has been associated with their psychosocial functioning [53].…”
Section: Discussionmentioning
confidence: 99%